Design and material selection for sustainable development of a novel double pass solar air heater with porous fins. (2022) - Khatri, Rahul; Goswami, Shlok; Anas, Mohd; Agarwal, Satvik; Sharma, Shyam Sunder
Abstract: Solar energy can be used for various household and commercial applications with solar air heater (SAH). Low thermal performance is a characteristic of solar energy systems. SAH performance can be improved with certain geometrical and surface modifications. The modifications in absorber surface and fluid flow region can improve the performance substantially. This study aims to design and develop a novel double pass solar air heater for higher thermal performance. The absorber surface geometry can improve the solar energy collection and heat transfer. The fluid passage if allowed above and below the absorber surface can substantially decrease the heat loss thus improving the thermal performance. A double pass single direction flow SAH with wavy shaped absorber plate is realized in this study. For improving the heat transfer porous cylindrical fins are also adapted over the top surface of the absorber plate. A high transmittance acrylic glazing is utilized to minimize the convection losses.